Positive Emotion Facilitates Cognitive Flexibility: An fMRI Study - Wang, Yanmei; Chen, Jie; Yue, Zhenzhu (Frontiers in Psychology, 2017)
Cognitive flexibility is the ability to switch rapidly between multiple goals. By using a task-switching paradigm, the present study investigated how positive emotion affected cognitive flexibility and the underlying neural mechanisms. After viewing pictures of different emotional valence (positive, negative or neutral), participants discriminated whether a target digit in a specific color was odd or even. After a series of trials, the color of target stimuli was changed, i.e. the switch condition. Switch costs were measured by the increase of reaction times (RTs) in the switch trials compared to those in the repeat trials. Behavior results indicated that switch costs significantly decreased in the positive emotional condition, and increased in the negative emotional condition, compared with those in the neutral condition. Imaging data revealed enhanced activation in the dorsal cingulate cortex (dACC) in switch trials than those in repeat trials. Moreover, the interaction between emotion condition (positive, negative, neutral) and trial type (repeat vs. switch) was significant. For switch trials, the activation of dACC decreased significantly in the positive condition, while increased significantly in the negative condition compared to neutral condition. By contrast, for repeat trials, no significant difference was observed for the activation of dACC among three emotional conditions. Our results showed that positive emotions could increase the cognitive flexibility and reduce the conflict by decreasing the activation of dACC.